2012
DOI: 10.1007/s10620-012-2372-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Neuromuscular Function in Crohn’s Disease Patients Is Not Associated with Low Serum Vitamin D Levels

Abstract: Crohn's disease patients with sufficient vitamin D levels experienced a 43 % greater extension peak torque. Although vitamin D deficiency has been associated with neuromuscular dysfunction, there were no differences in serum vitamin D levels between the CD and healthy controls to explain the decreased muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…In this issue, Salacinski et al [5] have objectively demonstrated reduced lower limb muscle strength in subjects with Crohn's disease (CD) compared to healthy controls, confirming the work of previous studies [6,7]. However, the study was unable to show that this reduced strength was directly attributable to lower vitamin D (25-(OH) or vitamin D3) levels in CD subjects as originally hypothesized.…”
Section: Introductionsupporting
confidence: 62%
“…In this issue, Salacinski et al [5] have objectively demonstrated reduced lower limb muscle strength in subjects with Crohn's disease (CD) compared to healthy controls, confirming the work of previous studies [6,7]. However, the study was unable to show that this reduced strength was directly attributable to lower vitamin D (25-(OH) or vitamin D3) levels in CD subjects as originally hypothesized.…”
Section: Introductionsupporting
confidence: 62%
“…Table 1 shows that the quality scores of the included studies ranged from 2 to 7, with a median of 5. Thirty-two studies [16, 18, 2931, 3335, 3740, 44, 45, 4749, 51, 52, 54, 55, 61, 62, 6466, 70, 7377] were considered high quality and the others [2528, 31, 36, 4143, 46, 50, 53, 5660, 63, 6769, 71, 72] were low quality.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 31 studies [16, 25, 29, 3136, 43, 44, 46, 49, 5355, 57, 6066, 6872, 76, 77] were conducted on serum 25(OH)D levels in CD and healthy controls, and we conducted a meta-analysis of 29 effect values. We found mean serum 25(OH)D levels in patients with CD were significantly lower than in healthy controls (MD: − 3.17 ng/mL; 95% CI − 4.42 to − 1.93) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reversal of sarcopenia amongst 19 patients with active CD was recently demonstrated following infliximab administration, which correlated with a reduction in serum IL‐6 . Optimisation of nutritional status, in particular vitamin D, has an important role in muscle function . Small studies have shown that exercise may improve quality of life and clinical disease activity indices in outpatients with IBD .…”
Section: Discussionmentioning
confidence: 99%